PENGARUH KUALITAS TINGKAT PENERANGAN LAMPU, LINGKUNGAN KERJA DAN PERALATAN TERHADAP PRODUKTIVITAS KERJA TEKNISI REPARASI ELEKTRONIK DI WILAYAH KABUPATEN BADUNG - Teresna, I Wayan; Suhantono, Djoko (BULETIN FISIKA; Vol 13 No 2 (2012): BULETIN FISIKA, 2012)
Quality level of illumination, work environment and equipment is one of the principal indicator in determining productivity. This paper presents the results of research on electronic technician answers as respondents in Badung on the effects of lighting levels, work environment and work productivity tools. As the analysis used include correlation test, test and test simultaneous partial t F. Based on the results of this study tests the hypothesis that the correlations obtained between the productivity level of illumination is very weak, then the working environment and equipment also has a very weak correlation. While partially test the hypothesis that the level of illumination has no effect on labor productivity electronics technician, as well as the working environment and equipment has no effect on labor productivity technicians. If the F test simultaneously at the level of illumination, the working environment and equipment also had an influence on productivity of electronics technician working in Badung.